Early Detection of Hydrogen Leakage Using Fiber Optic Hydrogen Sensor Based on WO3-PdPt-Pt Nanocomposite Films - Jixiang Dai; Zhangning Chen; Rundong Yang; Zhouyang Wu; Zhengan Tang; Wenbin Hu; Cheng Cheng; Xuewen Wang; Minghong Yang (Nanomaterials)
Quickly detecting hydrogen leakage is crucial to provide early warning for taking emergency measures to avoid personnel casualties and explosion accidents in hydrogen energy fields. Here, a compact optical fiber hydrogen sensing system with high sensitivity and quick response rate is proposed in this work. A laser diode (LD) and two photodetectors (PD) are employed as light source and optical signal transformation devices, respectively. This sensing system employs single-mode optical fiber deposited with WO3-PdPt-Pt nanocomposite film system as sensing element. Under irrigating power of 6 mW, the sensing probe exhibits an ultra-fast response to hydrogen concentrations of 4000 ppm and 10,000 ppm, with response times of 0.44 s and 0.34 s, respectively. In addition, detection limit of 3 ppm can be achieved by using this sensing system. The sensor also shows good repeatability during hydrogen exposure of 3~10,000 ppm, demonstrating its great potential application for hydrogen leakage in hydrogen energy facilities.